Integrated Cash Waqf and Islamic Microfinance to Poverty Alleviate - Ahmad, Rusyda Afifah; Mafaza, Syofi Aruni; Handayani, Resi (El-Barka Journal of Islamic Economics and Business, 2021)
Cash Waqf is a trust fund established with money to support services to humankind on behalf of Allah SWT. Efforts to maximize the use of cash waqf funds have the potential to improve the welfare of the community, especially in alleviating the poor. One of the institutions in this field is the Islamic microfinance institution. These Islamic microfinance institutions include Baitul Maal (social funds) and Baitu Tamwil (commercial) and cooperatives. This Islamic microfinance institution is a facility for the poor to develop their business. The research method used in this research is a literature survey of more than 20 articles. Not only analyzing empirically and comparatively but also provide recommendations and suggestions with several theoretical works. The results of this study indicate that cash waqf has been widely practiced and could become a financing facility for MSMEs to alleviate poverty.Wakaf Tunai adalah dana amanah yang didirikan dengan uang untuk mendukung layanan kepada umat manusia atas nama Allah SWT. Upaya memaksimalkan penggunaan dana wakaf tunai berpotensi untuk meningkatkan kesejahteraan masyarakat, terutama dalam pengentasan masyarakat miskin. Salah satu lembaga di bidang ini adalah lembaga keuangan mikro syariah. Lembaga keuangan mikro syariah tersebut antara lain Baitul Maal (dana sosial) dan Baitu Tamwil (komersial) serta koperasi. Lembaga keuangan mikro syariah ini merupakan sarana bagi masyarakat miskin untuk mengembangkan usahanya. Metode penelitian yang digunakan dalam penelitian ini adalah survey literatur lebih dari 20 artikel, tidak hanya menganalisis secara empiris dan komparatif tetapi juga rekomendasi dan saran dengan beberapa karya teoritis. Hasil penelitian ini menunjukkan bahwa wakaf tunai telah banyak dilakukan dan mampu menjadi sarana pembiayaan bagi UMKM dengan tujuan untuk mengentaskan kemiskinan.